The Rhino-Lip-Lifting: A Novel Proposal for Midface Profileplasty Performed as a Single Surgical Procedure - Pascali, Michele; Marchese, Gloria; Diaspro, Alberto (Facial Plastic Surgery, 2021)
As facial aging occurs, aesthetic changes of the nasal tip and the senile upper lip include tip ptosis, increase in skin length, loss of vermillion height and Cupid's bow, and vertical wrinkles.Regardless of the rejuvenation procedure, the lips are not to be considered as a single anatomical entity, instead they should be placed in a strong correlation with the nose. The aim of this study is therefore to demonstrate the effectiveness of the association of primary closed rhinoplasty together with indirect subnasal lip-lifting technique.A total of 45 patients were enrolled in this study and underwent primary closed rhinoplasty with indirect subnasal lip-lifting. The result showed an overall average nasolabial angle width reduction of 10.9% and lip length shortening of 23.5%, as assessed 1 year after the surgical procedure. When comparing before and after photographs and using the Subjective Global Aesthetic Improvement Scale (sGAIS), the overall satisfaction was rated 4.4 on 5, as “much improved.”The authors show that lips should not be considered as a single anatomical entity but that they indeed must be placed in a strong correlation with the nose since a droopy nasal tip is likely to be considered unattractive and is often associated with the appearance of a long nose with covered philtrum and upper lip.Tip rotation to a normal nasolabial angle width could grant a beneficial impact on overall nose aesthetics; however, it may not fully balance the midface profile as it is the “lip position-to-incisal show” ratio that defines beauty, whereas the balance among forehead, nasal tip, upper lip, and chin is what defines the contour of harmonious profiles.This is the first patient series to show that the combination of closed rhinoplasty and indirect lip-lifting is a highly effective, safe, and reliable procedure to address profile rejuvenation.
Keywords: nose; lip; lifting